Post-Disaster Resilient Communication through Infrastructure-Free Networks - Ratna R. Sarkar; Amitabha Chakrabarty; Mohammad Zahidur Rahman (Journal of ICT Research and Applications, 2026)
Traditional communication systems are often disrupted during disasters, leaving communities disconnected and interrupting the exchange of essential information. In these circumstances, a reliable communication approach is critical for coordinating relief and recovery activities. This work presents a Resilient Communication Model (RCM), an infrastructure-free solution designed to enhance post-disaster communication. The model relies on dynamic, self-organizing links between nearby devices, allowing victims and rescuers to communicate effectively. Due to its lightweight and flexible design, the system is particularly well-suited for basic devices, which are more likely to remain functional in crisis conditions. Simulation studies and comparative evaluations with other algorithms demonstrate that the model minimizes packet loss ratios (PLR), delay, and enhances communication stability, packet delivery ratio (PDR) and throughput during network disruptions. Practical experiments across diverse scenarios further confirm the model’s feasibility and resilience. Overall, the findings demonstrate that the model can reliably function as a fallback communication system when standard networks are unavailable.